2017
DOI: 10.7554/elife.29118
|View full text |Cite
|
Sign up to set email alerts
|

Mcm10 promotes rapid isomerization of CMG-DNA for replisome bypass of lagging strand DNA blocks

Abstract: Replicative helicases in all cell types are hexameric rings that unwind DNA by steric exclusion in which the helicase encircles the tracking strand only and excludes the other strand from the ring. This mode of translocation allows helicases to bypass blocks on the strand that is excluded from the central channel. Unlike other replicative helicases, eukaryotic CMG helicase partially encircles duplex DNA at a forked junction and is stopped by a block on the non-tracking (lagging) strand. This report demonstrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 52 publications
(99 reference statements)
7
91
1
Order By: Relevance
“…In addition, recent studies have indicated that Pol δ sometimes extend the first leading strand primer at an origin before being taken over by Pol ϵ . In vitro assays have identified the minimal protein requirements for both leading and lagging strand synthesis, and for replication fork rates on chromatized DNA consistent with in vivo observations …”
Section: Cmg Helicase Is a Central Scaffold For Replisome Organizationmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, recent studies have indicated that Pol δ sometimes extend the first leading strand primer at an origin before being taken over by Pol ϵ . In vitro assays have identified the minimal protein requirements for both leading and lagging strand synthesis, and for replication fork rates on chromatized DNA consistent with in vivo observations …”
Section: Cmg Helicase Is a Central Scaffold For Replisome Organizationmentioning
confidence: 66%
“…Notably, ZF4 binds the future lagging strand in dsDNA, and therefore both strands of the duplex are engaged by CMG, and the unwinding point is at the top of the N‐tier, but just beneath the protruding ZFs, which likely explains inhibition of S.c. CMG by a lagging strand dual SA block . Interestingly, S.c. Mcm10 binds to CMG and enables S.c. CMG to rapidly traverse the dual SA lagging strand block by steric exclusion . The exact mechanism by which Mcm10 promotes this bypass is not yet understood.…”
Section: Cmg Binds Both Dsdna and Ssdna At A Forked Junctionmentioning
confidence: 99%
“…Enigmatic is also the function of the Mcm10 protein which has been involved in both replisome assembly and progression . Mcm10 associates to Mcm2‐7 and Cdc45 and has been proposed to stimulate CMG function and stabilize Pol α …”
Section: Architecture and Function Of The Eukaryotic Replisomementioning
confidence: 99%
“…In particular, studies have explored the consequence of placing obstacles on either the translocating or non‐translocating strand using origin replication assays conducted with λ‐phage DNA (Figure F) . Direct encounters between single helicases and steric blocks revealed that both X. laevis and S. cerevisiae CMGs are only affected by a biotin‐streptavidin block on the translocating strand and not the non‐translocating strand . A recent study demonstrates that Mcm10 is required to bypass blocks on the non‐translocating strand either by partial N‐tier ring opening or a dynamic transition between different helicase unwinding modes.…”
Section: Staged Assembly Ensures Robust Eukaryotic Dna Replicationmentioning
confidence: 99%
“…Direct encounters between single helicases and steric blocks revealed that both X. laevis and S. cerevisiae CMGs are only affected by a biotin‐streptavidin block on the translocating strand and not the non‐translocating strand . A recent study demonstrates that Mcm10 is required to bypass blocks on the non‐translocating strand either by partial N‐tier ring opening or a dynamic transition between different helicase unwinding modes. In addition to a classic steric exclusion mechanism, an alternative proposal involves dsDNA entering the N‐tier and unwinding in the central channel with strand extrusion occurring out the same N‐tier entry .…”
Section: Staged Assembly Ensures Robust Eukaryotic Dna Replicationmentioning
confidence: 99%